BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2003)
Oilseed Brassicas: Constraints and Their Management, T.P. Bhowmik (ISBN 81-239-0877-6), CBS Publishers, 4596/1-A, Darya Ganj, New Delhi 110 002, 2003, 254 pp, Rs.1295/-